Factors Associated with Prevention of Hypertension in Adolescents - Delyan Octafyananda; Novi Berliana; Sugiarto Sugiarto (Universitas Veteran Bangun Nusantara, 2021)
Currently, people with hypertension are not only experienced by someone who is elderly, but teenagers in particular have been diagnosed with hypertension. Data from the Jambi City Health Office in 2020 shows that the Paal Merah II Health Center is a health center that has the highest prevalence of hypertension, which is 7.54%. The purpose of the study was to determine the factors associated with the prevention of hypertension in adolescents. The study used a cross sectional approach. The study was conducted in the working area of the Paal Merah II Public Health Center, Jambi City, from June to July 2021. The research sample was teenagers aged 15-19 years as many as 59 people. The sampling technique used was purposive sampling technique. Data were analyzed by univariate and bivariate using chi square test. A total of 49.2% of respondents had poor hypertension prevention behavior, 44.1% of respondents had poor knowledge, 45.8% of respondents had poor attitudes, 47.5% of respondents had poor self-efficacy, 40.7% of respondents had poor self-efficacy. social media is not good and 47.5% of respondents have less good peers. The results of the bivariate analysis showed that there was a relationship between knowledge (p-value = 0.013), attitudes (p-value = 0.027), self-efficacy (p-value = 0.000), social media (p-value = 0.050) and peers (p-value = 0.050). value=0.013) with hypertension prevention in the work area of Paal Merah II Health Center. It is expected that adolescents can prevent hypertension well such as doing physical activity (exercise) regularly 2-3 times a week for 30 minutes, not smoking, not consuming fast food and being able to control emotions when there is a problem so as to reduce the risk of hypertension.